2002
DOI: 10.1530/eje.0.1470815
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic involvement in stress-induced vasopressin and oxytocin secretion

Abstract: Objective: To investigate the involvement of serotonin (5-hydroxytryptamine -5-HT) receptors in mediation of stress-induced arginine vasopressin (AVP) and oxytocin (OT) secretion in male rats. Design: Experiments on laboratory rats with control groups. Methods: Different stress paradigms were applied after pretreatment with intracerebroventricular infusion of saline or different 5-HT antagonists. Results: Restraint stress (5 min), hypotensive hemorrhage or dehydration for 24 h increased AVP secretion fivefold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 62 publications
1
31
0
1
Order By: Relevance
“…One potential source of stress is water deprivation, which increases the levels of hormones and proteins (c-Fos) that are associated with stress (Arnhold, Wotus, & Engeland, 2007;Jørgensen, Knigge, Kjaer, & Warberg, 2002). However, most studies have only looked at the initial effects of restricting an animal's water intake (e.g., 1 or 6 days as in the previously cited studies), and a longer-term study found that hormonal levels in rats on water restriction had returned to normal by 8 weeks (Sakellaris & Vernikos-Danellis, 1974).…”
Section: Tinnitus and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential source of stress is water deprivation, which increases the levels of hormones and proteins (c-Fos) that are associated with stress (Arnhold, Wotus, & Engeland, 2007;Jørgensen, Knigge, Kjaer, & Warberg, 2002). However, most studies have only looked at the initial effects of restricting an animal's water intake (e.g., 1 or 6 days as in the previously cited studies), and a longer-term study found that hormonal levels in rats on water restriction had returned to normal by 8 weeks (Sakellaris & Vernikos-Danellis, 1974).…”
Section: Tinnitus and Stressmentioning
confidence: 99%
“…Indeed, it is possible that the occasional reinstatement of tinnitus in some rats following anesthesia was due to the stress of being anesthetized rather than being a direct effect of the anesthesia itself. As previously noted, animals could be exposed to loud sound without anesthesia by restraining them, although they would have to be acclimated to this, because restraint itself can cause stress (e.g., Jørgensen et al, 2002)-and they would then hear the loud sound, which would also be stressful.…”
Section: Tinnitus and Stressmentioning
confidence: 99%
“…22,23 Jorgensen has also demonstrated that fluoxetine increases oxytocin and vasopressin release. The interconnection between these serotonin and neuropeptide systems opens up new avenues for psychopharmacological research.…”
Section: -21mentioning
confidence: 99%
“…Tg8/KO mice (a knockout strain for the monoamine oxidase-A gene, which presents high levels of NE OXT expression or release [57,58]. The involvement of 5-HT receptors in the mediation of stress-induced AVP and OXT secretion [59] or of NE receptors to in AVP secretion from the PVN in pain modulation [60] has also been identified. DA-ergic input has been observed in the PVN and SON.…”
Section: Monoaminergic Regulation Of the Avp-and Oxt-ergic Systemsmentioning
confidence: 99%